Unlocking the potential of blue food-and feed-centered marine biorefineries - Cakmak, Ece Kendir; Owusu-Agyeman, Isaac; Balkis, Nuray Caglar; Aksu, Abdullah; Taskin, Omer Suat; Cetintasoglu, Mehmet Emre; Cetecioglu, Zeynep (Elsevier, 2026)
The marine biorefinery concept, especially focusing on blue feed and food production, can be one of the key pillars to contribute to the Blue Economy. The secondary marine-based sources such as low-trophic organisms and marine industry waste such as fish processing and aquaculture waste can be utilized to extract carbohydrates, proteins, lipids, minerals and bio-active compounds that can be cascaded for the production of food packaging materials, food analogues and animal feed within the marine biorefinery concept to promote circular economy. This review explores the potential of these marine-based sources as raw materials not only for intermediate value-added products but also for three main related end-products: blue food, blue feed, and smart-active food packaging. The importance of environmental sustainability, techno-economic and social assessment to the implementation of these products in the concept of blue economy is also highlighted. This review illustrates the prospects of a blue economy based on secondary marine resources as a catalyst for a sustainable society and circular economy.
Keywords: Blue economy; Biorefinery; Food analogues; Smart packaging; Active packaging; Blue feed; Single cell protein